(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Optimism involves a power to resist all difficulties in order to maintain the life in an effective way in spite of all of its obstacles. Optimists are the masters of their own fate. They believe that good things will happen to them and that they can make good things happen. Adolescents live in a society which has become multi complex thus making the role of adolescents very diffuse and confusing. An adolescent struggle with the developmental tasks of establishing an identity,